Sustainable micro irrigation management for trees and vines - Goyal, Megh Raj (Apple Academic Press, 2014)
This valuable book, the third volume in the Research Advances in Sustainable Micro Irrigation series, focuses on sustainable micro irrigation management for trees and vines. It covers the principles as well as recent advances and applications of micro irrigation techniques.
Keywords: Irrigation.; Microirrigation -- History.; Microirrigation.; elektronické knihy; electronic books